A comparison between MRI, sonography and Functional Independence Score in Haemophilia methods in diagnosis, evaluation and classification of arthropathy in severe haemophilia A and B. Issue 2 (March 2016) - Tasbihi, Mandana; Pishdad, Parisa; Haghpanah, Sezaneh; Ardeshiri, Rezvan; Tavoosi, Hakimeh; Karimi, Mehran
Abstract : Evaluation of joints in children with haemophilia is important in detecting abnormalities, staging their severity and following the effects of treatment. The aim of this study is to evaluate the correlation of FISH score (Functional Independence Score in Haemophilia) with the scores obtained by MRI and sonography for the diagnosis, evaluation and classification of arthropathy in severe haemophilia. In this cross-sectional study on 25 severe haemophilia patients, FISH, MRI and sonography procedures were performed in the elbow or knee joint. All patients' information, including age, type of haemophilia, affected joint, scores of MRI, sonography and FISH, dose of factor consumed, weight and prophylaxis protocol were collected and analysed. Among the 25 patients (age range of 11–70 years), 22 patients were haemophilia A and three patients were haemophilia B. Affected joints were right knee in 12 patients, left knee in nine and right elbow in four. There was only a statistically significant negative correlation between FISH and MRI Additive (A) scale ( r s = −0.537, P = 0.006). Considering cartilage loss domain (related MRI A scale: 13–20), 20 patients (80%) were classified in this group with FISH scores ranged from 17 to 22. On the basis of our results, FISH scores in severe haemophilia patients were negatively correlated with MRI A scale. Also, it seems that a FISH score less than 22 could be considered as loss of cartilage; however, due to the small number of our patients, it needs further assessment in different populations.